Let's simplify step-by-step.<span><span><span><span>−12</span>−12</span>−<span>12x</span></span>+6</span><span>=<span><span><span><span><span><span>−12</span>+</span>−12</span>+</span>−<span>12x</span></span>+6</span></span>Combine Like Terms:<span>=<span><span><span><span>−12</span>+<span>−12</span></span>+<span>−<span>12x</span></span></span>+6</span></span><span>=<span><span>(<span>−<span>12x</span></span>)</span>+<span>(<span><span><span>−12</span>+<span>−12</span></span>+6</span>)</span></span></span><span>
=<span><span>−<span>12x</span></span>+<span>−<span>18</span></span></span></span>
Answer:
y + 13 = 5(x + 2)
Step-by-step explanation:
The slope-intercept form of the equation of a line is
y = mx + b,
where m = slope, and b = y-intercept.
From the slope-intercept equation y = 5x - 3, we see that the slope of the line is 3.
The point-slope form of the equation of a line is:
y - y1 = m(x - x1)
where m = slope, and (x1, y1) is a point on the line.
We have point (-2, -13), so x1 = -2, and y1 = -13.
We also have slope 5, so m = 5.
Now we use the coordinates of the given point and the slope in the point-slope equation.
y - (-13) = 5(x - (-2))
We simplify to get
y + 13 = 5(x + 2)
LCD(34, 45, 23) = LCM(4, 5, 3) = 22×3×5 = 60
34 = 4560
45 = 4860
23 = 4060
8 - 2x = -8x + 14 <em>subtract 8 from both sides</em>
-2x = -8x + 6 <em>add 8x to both sides</em>
6x = 6 <em>divide both sides by 6</em>
<h3>x = 1</h3>
In 2 hours,hope this helps :)